Human Cytomegalovirus Primary Infection and Reactivation: Insights From Virion-Carried Molecules - Wang, Yu-Qing; Zhao, Xiang-Yu (Frontiers in Microbiology, 2020)
Human cytomegalovirus (HCMV), a ubiquitous beta-herpesvirus, is able to establish lifelong latency after initial infection. Periodical reactivation occurs after immunosuppression, remaining a major cause of death in immunocompromised patients. HCMV has to reach a structural and functional balance with the host at its earliest entry. Virion-carried mediators are considered to play pivotal roles in viral adaptation into a new cellular environment upon entry. Additionally, one clear difference between primary infection and reactivation is the idea that virion-packaged factors are already formed such that those molecules can be used swiftly by the virus. In contrast, virion-carried mediators have to be transcribed and translated; thus, they are not readily available during reactivation. Hence, understanding virion-carried molecules helps to elucidate HCMV reactivation. In this article, the impact of virion-packaged molecules on viral structure, biological behavior, and viral life cycle will be reviewed.